Prawość apostoła w świetle Rz 9,1-5 - Żywica, Zdzisław (Collectanea Theologica, 2018)
The author shows how Paul creates the image of the righteous Apostle referring to arguments and witnesses in order to authenticate the self-portrait found in Rom 9,1-5 as well as the credibility of the arguments submitted; this is so also in section Rom 9,6–11,36. Paul carefully planned the rhetorical strategy and strengthened the arguments competently, as well as the authority and credibility of the witnesses cited. In the adopted rhetoric and theological strategy, he refers three times to the biblical legal tradition of the need to appoint two or three witnesses. He thus built the triple sequence of the next three testimonies: 1. “I say the truth in Christ”; 2. “I’m not lying; 3. “My conscience in the Holy Spirit testifies to my conscience.” Then he presented three witnesses with the highest authority and credibility: 1. God in Christ; 2. The conscience of the Apostle; 3. The Holy Spirit. Throughout the section, the quoted texts are cited from three great biblical traditions: 1. legal; 2. prophetic; 3. sapiential. Therefore, the Apostle consistently presented the maximum number of witnesses (three), additionally multiplied by three autonomous circles.